Dysregulated Coagulation in Parkinson’s Disease - Xinqing Wang; Wenxin Li; Xinyue Zhao; Ning Hu; Xi Wang; Xilin Xiao; Kai Yang; Taolei Sun (Cells)
Parkinson’s disease (PD), a prevalent neurodegenerative disorder characterized by dopaminergic neuron degeneration and α-synuclein accumulation, has been increasingly associated with coagulation dysfunction. This review synthesizes emerging evidence linking dysregulated coagulation to PD pathophysiology. We examine the alterations in coagulation parameters, including elevated fibrinogen levels, impaired fibrinolysis, and platelet dysfunction, which collectively contribute to a hypercoagulable state in PD patients. Epidemiological studies have revealed a higher incidence of thrombotic events, such as deep vein thrombosis (DVT) and stroke, among PD patients, suggesting significant comorbidity between PD and coagulation disorders. This review explores the potential pathophysiological mechanisms underlying this association, focusing on the roles of inflammation and oxidative stress. Additionally, we discuss the limitations of current research and propose future directions. This comprehensive analysis underscores the importance of understanding the coagulation–neurodegeneration axis in PD, which may lead to novel diagnostic and therapeutic strategies for this debilitating condition.